Judicial Review Peraturan Pemerintah Pengganti Undang-Undang (Perppu) oleh Mahkamah Konstitusi Perspektif Fiqh Dusturiyah - Islahuddin, Muhammad (AHKAM, 2023)
In this study, the author takes the title Judicial review of Government Regulations in Lieu of Laws (PERPPU) by the Constitutional Court from the Fiqh Dusturiyah Perspective. The issue raised in this paper is whether the Constitutional Court has the authority to conduct a judicial review of a Perppu. The research objective of this paper is to find out and study the authority of the Constitutional Court in conducting a judicial review of the Perppu. The type of research used in this research is normative legal research. The approach used in this study is the legal political approach. The data used in this study is secondary data consisting of primary legal materials and secondary legal materials. Legal research uses the deductive thinking method, which means a method of thinking that begins and begins with general propositions that have been recognized for their truth and ends with a specific conclusion. The results of this study conclude that the Constitutional Court has the authority to examine the Perpu for several reasons. Starting from a sociological and teleological interpretation, it is very likely that the Perpu will contain material that contradicts the 1945 Constitution of the Republic of Indonesia or violates people's rights, without being able to be examined before being discussed by the DPR, so it is best if the Constitutional Court can conduct a judicial review of the Perpu. Judicial review of the Perpu by the Constitutional Court is also in the context of upholding the principles of the Indonesian legal state and the supremacy of the constitution. In siyasash fiqh studies, there is a judiciary institution known as the Al-Mazalim Region, which specifically deals with the tyranny of the rulers against the people, including in making policies or laws. The judiciary of the al-Mazalim Region resembles the Constitutional Court in terms of safeguarding people's rights which may be violated through the making of policies or laws. In line with the conclusions above, it is best if the law-making bodies, in this case the DPR and the President, immediately fill in the legal vacuum regarding the judicial review of the Perpu by the Constitutional Court.